Pengaruh Displin dan Motivasi Kerja Serta Komitmen Organisasi terhadap Kinerja Dosen Sekolah Tinggi Agama Islam (STAI) Samora Pematangsiantar - Lydia Madona (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The purpose of this study is to look at how discipline, work motivation, and organizational commitment affect the performance of STAI Samora Pematangsiantar lecturers, either partially or concurrently. This study employs the dissemination of questionnaires as well as a quantitative method to research. Multiple linear regression analysis was utilized, as well as hypothesis testing (F-test, t-test, and coefficient of determination) (R2). In this study, 49 lecturers were used as a sample. The information in this study is based on primary sources. A questionnaire was used to gather information. The F-test was employed in conjunction with the t-test to test the hypothesis. The findings of the t-test of work discipline style have a significant impact on lecturer performance, motivation, and organizational commitment. Meanwhile, the F-test results, discipline and job motivation, as well as organizational commitment, all have an impact on lecturers' performance. According to the Coefficient of Determination (R2), X1, X2, and X3 account for 57.4% of the lecturer's performance, with the remaining 42.6 percent impacted by other variables.